2003
DOI: 10.1152/ajpgi.00521.2002
|View full text |Cite
|
Sign up to set email alerts
|

Central and noncentral blood volumes in cirrhosis: relationship to anthropometrics and gender

Abstract: .-The size of the central and arterial blood volume (CBV) is essential in the understanding of fluid retention in cirrhosis. Previously, it has been reported decreased, normal, or increased, but no reports have analyzed CBV with respect to gender and lean body mass. The aim of the present study was by means of an optimized technique to reassess it in a large group of patients with cirrhosis compared with healthy controls and matched controls in relationship to their body dimensions and gender. Eighty-three pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 32 publications
2
42
0
1
Order By: Relevance
“…Vasodilatation appears in the splanchnic area while vasoconstriction is present in the kidneys. These conditions are responsible for the decreased effective central blood volume [9,12]. High concentration of vasodilators and reduced sensitivity to vasoconstrictors play an important role in the genesis of vasodilatation in patients with cirrhosis known to be caused by various substances.…”
Section: Role Of the Vascular Tone In The Genesis Of Cirrhotic Cardiomentioning
confidence: 99%
“…Vasodilatation appears in the splanchnic area while vasoconstriction is present in the kidneys. These conditions are responsible for the decreased effective central blood volume [9,12]. High concentration of vasodilators and reduced sensitivity to vasoconstrictors play an important role in the genesis of vasodilatation in patients with cirrhosis known to be caused by various substances.…”
Section: Role Of the Vascular Tone In The Genesis Of Cirrhotic Cardiomentioning
confidence: 99%
“…Patients with cirrhosis have increased blood and plasma volumes [8,10]. The distribution of the blood to the different vascular beds is abnormal as it relates to the severity of disease [38-40,41•].…”
Section: Blood Volume Distributionmentioning
confidence: 99%
“…The distribution of the blood to the different vascular beds is abnormal as it relates to the severity of disease [38-40,41•]. Moreover, dynamic, as well as static, techniques have revealed that the central (thoracic) blood volume is most often decreased, whereas the non-central (especially splanchnic) blood volume is increased in patients with cirrhosis [10,38]. The effective arterial blood volume is decreased, and the abnormal volume distribution contributes to the systemic circulatory derangement [41•].…”
Section: Blood Volume Distributionmentioning
confidence: 99%
“…He et al [29] had already reported similar results, but the difference was not statistically significant. We hypothesize that there may be some differences as to etiopathogenesis, disease severity and gender distribution among the cirrhotic patients in previous studies [5,30,31] . The patients enrolled in our study (women/men: 9/30) had a cirrhosis mostly MTT in a control subject (A) was higher than in a cirrhotic patient (B).…”
Section: Groupmentioning
confidence: 95%